Philippine development plan 2011-2016. (National Economic and Development Authority, 2011)
"The Philippine Development Plan 2011-2016 was formulated in accordance with the Constitutional provision of Section 9, Article VII, directing the Government?s economic and planning agency to "implement a continuing integrated and coordinated programs and policies for national development." Upon the assumption of President Benigno S. Aquino III of the country?s leadership, he embarked on his program of government that is based on his "Social Contract with the Filipino People" wherein he articulated a commitment to transformational leadership, institutional reform, economic stability and inclusive growth... The Philippine Development Plan provides a substantive translation of the Administration?s Social Contract. The support of all sectors of society will be crucial in turning our aspirations for a better quality of life for all Filipinos into reality."--Preface.